Ajaran Tasawuf dalam Naskah Makamat - Zakiyah Zakiyah (Jurnal Lektur Keagamaan, 2014)
This paper concerns on the mysticism teaching in the manuscript entitled Makamat. The objective of this study is to describe the physical condition of the manuscript and to analyze the content of the texts in the manuscripts. To examine these contents, it uses meaning analysis. Meanwhile, to describe the physical condition of the manuscript, it employs codicology. Finding of this research shows that generally the manuscript is in a good condition and readable. It consists of four texts, and the first text was chosen as the focus of this study. It reveals that there are philosophical explanations on the basic knowledge of fiqh including wudlu, thaharah and shalat (prayer). These elements of the fiqh contain several deep meaning related to the mysticism.Keywords: Makamat, tasawuf, fiqh, manuscript.